Rutinan Maulid ŻibᾹ’ di Pondok Pesantren Al-Munawwir Komplek Nurussalam Putri Yogyakarta - Risda Alfi Fat Hanna; Saddam Husein; Eztika Azzara Aji; Tri Budi Prastyo (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This research aims to discuss the routine of Maulid ŻibᾹ' at Pondok Pesantren Al-Munawwir Nurussalam Putri Yogyakarta Complex. ndok Pesantren Al-Munawwir Complex Nurussalam Putri Yogyakarta. This type of research is field research with qualitative methods. In understanding the maulid phenomenon ŻibᾹ', the approach used is the Fairclough approach. This approach will examine socio-cultural aspects that have a certain meaning of the phenomenon. The results explained that the existence of open social interaction between boarding schools and santri resulted in a new culture, namely the reading of Maulid ŻibᾹ'. From the reading of shalawat ŻibᾹ' routinely causes the manager to create binding rules and force santri, following the reading of Maulid ŻibᾹ'. The recitation of Maulid ŻibᾹ' is a form of praise, respect and love to the Prophet (peace be upon him). Maulid ŻibᾹ' is also a shalawat that does not contradict the prophet's hadiths. The conclusion of this study is that the existence of open social interactions gives rise to a new culture, namely Maulid ŻibᾹ'. The caretaker who is the right hand of the caregiver also has the power in regulating the santri. So, no wonder when there are santri who carry out the routine of Maulid ŻibᾹ' not only because of respect for the Prophet Muhammad Saw. This routine is also based on QS. Al-Ahzab verse 56 and HR. Muslim No. 911 and 577. The authors recommend further research into the benefits of Maulid ŻibᾹ' in detail.